The food pharmacy : dramatic new evidence that food is your best medicine - Jean Carper (Toronto New York Bantam Books, 1988)
More than fifty common foods and their ability to relieve pain, destroy cholesterol, lower blood pressure, and fight infection are highlighted in a practical guide to good health through proper nutrition
Includes index.
Bibliography: p. 328-349.
Keywords: Herbs -- Therapeutic use; Natural foods -- Therapeutic use; Raw foods -- Therapeutic use